How Customer Satisfaction Can Mediate The Effect of Profit Sharing Ratio and Service Quality on Customer Loyalty - Wartoyo, Wartoyo; Maulidina, Devrina; Haerisma, Alvien Septian (Faculty of Islamic Economics and Business, UIN Prof. K. H. Saifuddin Zuhri Purwokerto, 2024)
Abstract This research aims to analyze the effect of profit sharing ratio and service quality on member loyalty with satisfaction as a mediating variable at the Sumber branch of BMT Al Falah. The research method used is quantitative by collecting data through questionnaires. Sampling was carried out using the probability sampling method using simple random sampling. The analytical method used is path analysis. The results of the research show that the profit sharing ratio has no significant effect on member loyalty with a significant value of 0.670 > 0.05, service quality has a positive and significant effect on member loyalty with a significant value of 0.033 < 0.05, the profit sharing ratio has no significant effect. on member loyalty with satisfaction as a mediating variable with a calculated t value of 1.422 < t table 1.66088, and service quality has a positive and significant effect on loyalty with satisfaction as a mediating variable with a calculated t value of 2.485 > 1.6608.